Factors associated with Prolonged Inaction in the hypoglycaemic treatment in people with non-insulin dependent Type 2 Diabetes and elevated glycated haemoglobin: A registry-based cohort study. Issue 5 (October 2017) - Goderis, Geert; Vaes, Bert; Van den Akker, Marjan; Elli, Steven; Mathieu, Chantal; Buntinx, Frank; Henrard, Séverine
Highlights: Prolonged Inaction (PI) is defined as the absence of antidiabetic treatment adjustments in spite of indications based on patients' HbA1c values. PI which is the sum of 'True' and 'False' Clinical Inertia is useful to evaluate patients' trajectories based on routinely collected data. PI in primary care is associated with both outcome indicators (lower values HbA1c values) and process indicators (higher frequency in the follow-up). The trigger to initiate antidiabetic treatment changes in 'real practice' remains 7.5% or even 8%, instead of 7%. Co-morbidities interact in a complex way, eitherer fostering PI (e.g. CKD) or fostering treatment intensification (e.g. depression). Abstract: Aims: To assess factors associated with Prolonged Inaction (PI) in insulin-naïve patients with Type 2 Diabetes Mellitus (T2DM). PI was defined as the absence of treatment initiation or intensification for ≥12 months despite HbA1c >7% (53 mmol/mol). Methods: A retrospective cohort study was conducted based on data from Intego, a Flemish General Practice registry. The study period ranged from January 1, 2006 to December 31, 2013. Patients with insulin therapy before the start of the study period were excluded from the analysis. A mixed effects logistic regression was used to assess the association of PI with the presence of co-morbidities, co-medications, process parameters and bio-clinical parameters. Results: In a population of 2265 patients with T2DM, 578 insulin-naive patients presented with an HbA1c >7% (53 mmol/mol) for ≥12 months. Median follow-up was 1.2 years, median age 67 years, 55% were male. PI was present in 340 patients (59%) and associated with moderate to severe Chronic Kidney Disease, absence of a mental health disorder, less frequent HbA1c measurements, lower HbA1c values and a smaller number of co-medications. Conclusions: PI is highly prevalent in primary care, particularly in patients with less complex disease status and with less intensive follow-up.